Pengaruh social system dan technical system terhadap purchase intention: peran engagement, desire to postpone closure dan product relevance pada short format video di TikTok - Carolin, Fela; Kurniawati, Masmira (Jurnal Ilmu Manajemen, 2025)
This study analyses the influence of social and technical systems on purchase intention by examining the role of engagement, desire to postpone closure, and product relevance on purchase intention on the TikTok social commerce platform. TikTok is one of the leading platforms with more than 1 billion users. It combines social media and e-commerce, allowing users to search for and buy products through short video formats. The research method used is a quantitative approach with an explanatory research design involving 167 respondents selected using purposive sampling. The results of this study indicate that entertainment and social interaction have a positive and significant effect on engagement, product visibility and recommendation have a positive and significant effect on desire to postpone closure, and recommendation also has a positive and significant effect on product relevance. While entertainment and social interaction do not significantly affect desire to postpone closure. however, engagement and desire to postpone closure as mediating variables significantly affect purchase intention. While product relevance as a mediating variable does not significantly affect purchase intention, product relevance can mediate the influence of the recommendation algorithm on desire to postpone closure. This study provides valuable insights for marketers and advertisers in designing effective marketing strategies on the TikTok platform.